VSTO 3.0 for Office 2007 programming: get to grips with programming Office 2007 using Visual Studio Tools for Office - Thangaswamy, Vivek (PACKT Publishing, 2009)
With the arrival of Visual Studio Tools for Office 3.0 (VSTO), developers can now program Microsoft Office from the .NET framework. There are huge books in the market that give loads of unnecessary information but are of no real help to brand-new Office developers. Wouldn't it be great to have a precise book that simply covers the basics and introduces programming Office 2007 with VSTO using the latest version of Visual Studio? This is that book. VSTO 3.0 for Office 2007 Programming shows you how to write Office 2007 applications with Visual Studio Tools for Office 3.0. Learn how to automate tasks in InfoPath, Word, Excel, Outlook, PowerPoint, Visio, and Project 2007 with greater programming power and flexibility than was available from the VBA language. With this book and the mastery of VSTO you will learn, Office will no longer be an application to you; it will be a platform for developing custom applications. VSTO 3 is the most recent version of VSTO, making use of Visual Studio 2008, and working with Office 2007. This book shows how VSTO puts Office automation into the hands of developers, allowing them to use the power of the .NET framework to automate Office applications thus increasing the speed of the applications, their security, and the opportunity to use other parts of the .NET Framework such as its data handling capabilities. This book builds a solid programming foundation in VSTO for brand-new Office developers. You will leave behind the world of VBA programming and take your first steps into the powerful and exciting world of using C# to create Office 2007 applications. Packed with examples and covering all the main Office applications, this book will have you creating fully featured Office extensions before you know it.